Chromosome Segregation Proteins as Coordinators of Cell Cycle in Response to Environmental Conditions - Pióro, Monika; Jakimowicz, Dagmara (Frontiers in Microbiology, 2020)
Chromosome segregation is a crucial stage of the cell cycle. In general, proteins involved in this process are DNA-binding proteins, and in most bacteria, ParA and ParB are the main players; however, some bacteria manage this process by employing other proteins, such as condensins. The dynamic interaction between ParA and ParB drives movement and exerts positioning of the chromosomal origin of replication (oriC) within the cell. In addition, both ParA and ParB were shown to interact with the other proteins, including those involved in cell division or cell elongation. The significance of these interactions for the progression of the cell cycle is currently under investigation. Remarkably, DNA binding by ParA and ParB as well as their interactions with protein partners conceivably may be modulated by intra- and extracellular conditions. This notion provokes the question of whether chromosome segregation can be regarded as a regulatory stage of the cell cycle. To address this question, we discuss how environmental conditions affect chromosome segregation and how segregation proteins influence other cell cycle processes.